High toughness carbon-nanotube-reinforced ceramics via ion-beam engineering of interfaces. (15th August 2020) - Athanasiou, Christos E.; Zhang, Hongliang; Ramirez, Cristina; Xi, Jianqi; Baba, Tomonori; Wang, Xing; Zhang, Wei; Padture, Nitin P.; Szlufarska, Izabela; Sheldon, Brian W.
Abstract: In nanocomposites, improved mechanical performance is critically linked to understanding and controlling interfacial properties. In the work reported here, ion implantation is introduced as a new method for tailoring the complex nanoscale interfaces between multiwall carbon nanotubes (MWCNTs) and a ceramic matrix. The results show that surface layers of the nanocomposite with high toughness can be created with C 2+ ions. This enhanced toughening due to ion implantation is associated with large compressive stresses in the MWCNTs and with significant changes in the carbon structure. These observations are consistent with molecular dynamics (MD) simulations, which indicate that partial amorphization of the MWCNTs is enhanced by the compressive stress and confinement within the ceramic matrix. This work opens up new opportunities for using ion implantation to create a new class of exceptionally tough ceramic nanocomposites. Graphical abstract: Image 1